2019
DOI: 10.1016/j.actamat.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Short-range order structure motifs learned from an atomistic model of a Zr50Cu45Al5 metallic glass

Abstract: The structural motifs of a Zr50Cu45Al5 metallic glass were learned from atomistic models using a new structure analysis method called motif extraction that employs point-pattern matching and machine learning clustering techniques. The motifs are the nearest-neighbor building blocks of the glass and reveal a well-defined hierarchy of structures as a function of coordination number. Some of the motifs are icosahedral or quasi-icosahedral in structure, while others take on the structure of the most close-packed g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Their origin is now discussed. Recent molecular dynamics (MD) simulations showed that at the glass transition the motif distribution in metal-metal MGs changed towards an increase in "icosahedral-like" order in the supercooled liquid 63 . On the other hand, for metalmetalloid MGs the influence of covalent bonding seems to be the key parameter leading to a frustration of icosahedral structures 7,58,[64][65][66] .…”
Section: A Calorimetric Observations By Dsc and Ppmsmentioning
confidence: 99%
“…Their origin is now discussed. Recent molecular dynamics (MD) simulations showed that at the glass transition the motif distribution in metal-metal MGs changed towards an increase in "icosahedral-like" order in the supercooled liquid 63 . On the other hand, for metalmetalloid MGs the influence of covalent bonding seems to be the key parameter leading to a frustration of icosahedral structures 7,58,[64][65][66] .…”
Section: A Calorimetric Observations By Dsc and Ppmsmentioning
confidence: 99%
“…geometrical differences can be resolved by motif extraction, which revealed that a collection of motifs coexist in the MG system and each motif possesses a certain population and a propensity of motion[64][65][66][67]. The glass transition or a plastic deformation process should be accompanied by a geometrical change of the motif configuration, resulting in an increase or decrease of the population of specific motifs, and should also be simultaneously accompanied by a change of the correlation length of motifs (i.e.…”
mentioning
confidence: 99%
“…A molecular dynamics (MD) simulation came to a similar conclusion, finding the coexistence of P-centered polyhedra, that is tricapped trigonal prisms, and densely packed Ni-centered icosahedra leading to a topological order between these two clusters 44 . Furthermore, it was observed by another MD simulation combined with the recently developed motif extraction that for some motifs the population was strongly altered by by-passing the glass transition using an ultrafast cooling 45,46 . It seems that for the metal-metalloid case, a bicapped square antiprism motif (in addition to the icosahedral motif 45 ) plays a significant role in the glass transition 46 .…”
Section: Modelsmentioning
confidence: 99%
“…Furthermore, it was observed by another MD simulation combined with the recently developed motif extraction that for some motifs the population was strongly altered by by-passing the glass transition using an ultrafast cooling 45,46 . It seems that for the metal-metalloid case, a bicapped square antiprism motif (in addition to the icosahedral motif 45 ) plays a significant role in the glass transition 46 . The influence of covalent bonding seems to be the key parameter for the frustration of icosahedral structures 46,47 .…”
Section: Modelsmentioning
confidence: 99%